Pengaruh Pemenuhan Penyisihan Penghapusan Aktiva Produktif Dan Non Performing Financing Terhadap Return On Asset Pada PT. Bank Syariah Mandiri - Saiful, Salman; Lubis, Santi; Sari, Ratna (Proceedings of International Conference on Islamic Economic Finance and Social Finance (ISSN: XXXX-XXXX) (ESSN: XXXX-XXXX), 2023)
Based on ROA (Return On Asset) data at PT. Bank Syariah Mandiri for the period 2006 to 2014, there were fluctuations that did not correspond to the increase and decrease in the fulfillment of Allowance for Productive Asset Write-Offs, namely in 2008, 2009, 2011, 2012, and 2013 and Non Performing Financing, namely in 2010, 2011, and 2012. So the formulation of the problem in this study is whether Allowance for Productive Asset Write-Offs and Non Performing Financing partially and simultaneously affect Return On Assets at PT. Bank Syariah Mandiri Tbk. The purpose of this study is to determine the effect of PPAP (Provision for Productive Asset Write-Offs) and NPF (Non Performing Financing) partially and simultaneously on ROA (Return On Assets) at PT. Bank Syariah Mandiri Tbk. This research is a quantitative research, using secondary data and time series form from 2006 to 2014 as many as 36 samples. Data analysis used is descriptive, normality test, linearity test, classical assumption test, multiple linear regression test, determination coefficient test (R2), partial significance test (t test) and simultaneous significance test (F test). The results of the study partially (t test). PPAP fulfillment has no effect and is not significant on ROA as evidenced by tcount ? ttable partially has a significant effect on ROA as evidenced by tcount ? ttable. While simultaneously PPAP and NPF fulfillment simultaneously have an effect on ROA.